Engineering factors as a decision model for choosing the type of renewable energy power plant establishment in Thailand - Songkrit Trerutpicharn; Waranon Kongsong; Kijbodi Kongbenjapuch (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The objective of this article is to propose the approach about engineering factors as a decision model for choosing the type of renewable energy power plant establishment in Thailand with supporting information to increase the number of renewable energy power plant establishments. Reducing energy consumption through the government and energy development from renewable energy plays an important role to strengthen the energy security for the country by increasing economic stability. To conserve the environment and reduce the use of energy from fossils, which is one of the main causes of global warming, the literature about acceptance, consisting of attitude related to usage, performance expectations, expectations of use, social influence, environmental support and government policy with analysis of decision models including interest in products, desire for products, product knowledge and the possibility to buy in the future to create energy security for the country, was reviewed. The government is making an effort to encourage the private sector to install electricity generation systems using renewable energy with support in various fields, including tax measures and the providing of various benefits to create investment incentives, such as academic information support, import duty exemption on raw materials for solar panels, support with funding loans, and revolving funds through financial institutions.